Progress of Resin Industry in Uttar Pradesh - Upadhyay, M. D. (Indian Forester, 1957)
Resin work was started in Uttar Pradesh in 1896 and since then there has been steady increase in the yield of crude resin and consequently in the production of rosin and turpentine also. There have been some improvements in the method of tapping. Some experiments were also carried out to find out various methods of increasing yield of resin, rate of occlusion, effect of tapping trees below 3Â½ ft. g.b.h., etc. A large amount of revenue is derived from resin in U.P. Resin is the biggest industry of Kumaun, it provides employment to about 10,000 persons and about Rupees 25 lacs are paid annually as wages.